2006
DOI: 10.1262/jrd.17111
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of .ALPHA.v.BETA.3 and .ALPHA.v.BETA.5 Integrin mRNA in Mouse Fetal Gonads

Abstract: Abstract. The αvβ3 and αvβ5 integrins are known as transmembrane receptors capable of binding to the RGD amino acid peptide sequence. In mouse early gonadogenesis, some proteins containing the RGD sequence are deposited into extracellular space and participate in morphogenesis. We analyzed the expression patterns of the αvβ3 and αvβ5 integrins in mouse developing gonads (10.5-13.5 days post coitum) using whole-mount in situ hybridization. The αv integrin mRNA was homogenously expressed in developing gonadal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Integrins are essential for PGC functionality [40], [41] and it has been reported that the absence of Prnp may be compensated by these proteins [42], [43]. Since integrin signalling is crucial in promoting mouse ESC self-renewal [44], we speculated that Prnp expression might also be related to this integrin expression during ESC differentiation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Integrins are essential for PGC functionality [40], [41] and it has been reported that the absence of Prnp may be compensated by these proteins [42], [43]. Since integrin signalling is crucial in promoting mouse ESC self-renewal [44], we speculated that Prnp expression might also be related to this integrin expression during ESC differentiation.…”
Section: Resultsmentioning
confidence: 96%
“…8A). Interestingly, mRNA for Itgb5 , described to be a gonadal tissue marker [41], appeared in higher amounts in the WT ESC than in the KO ESC; however, expression was higher in the PGC-like KO EBs at all the differentiation times (Fig. 8A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously reported [19] that the ECM remodeling of enzymes matrix metalloproteinases (mmp2 and mmp3) and ECM proteins, including collagens, proteoglycans, and glycoproteins, were highly expressed in testicular ECM when testicular fusion occurred. During gonadal morphogenesis, integrin plays a variety of critical roles in cell migration, differentiation, and connection between the germ and somatic or somatic and somatic cells [16]. It is yet unknown how interactions and cellular signaling between these glycoproteins and integrins control gonadal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the integrin β6 subunit is specifically expressed in epithelial cells [12,13] and plays key roles in regulating cell adhesion and the migration of cancer disease [14,15]. During the early gonadogenesis of mice, the primordial germ cells specifically expressed integrin beta3 [16] and played roles in cell adhesion during the theca cell layer formation in mouse ovarian follicles [17]. In the mouse ovary, integrin beta5 mRNA was primarily expressed in the granulosa cells of follicles [18,19], which suggested that integrin could play a function in granulosa cell proliferation.…”
Section: Introductionmentioning
confidence: 99%